Case Book for MD( Anaesthesiology ) Part II - De Alwis, N.A.V.C.T (My University, 2000)
Anaesthetic management of a patient undergoing one lung anaesthesia for resection of a mediastinal Tumour ; Anaesthetic management of a patient for Renal transplantation,; Intensive care management of a patient with eclampsia and HELLP syndrome; Intensive care management of a patient with eclampsia and HELLP syndrome; Microlaryngoscopic polypectomy, General anaesthesia for ; Phaeochromocytoma, Anaesthetic management of a patient for excision of ; Rheumatoid arthritis for total hip replacement, Anaesthetic management of a patient with ; Intensive care management of a patient with chest trauma; Chest trauma, Intensive care management of a patient with ; Laparoscopic cholecystectomy, Anaesthetic management of a patient ; Cerebral aneurysm, Anaesthetic management of a patient for clipping of a ; Fistula, Anaesthetic management of a neonate for repair of tracheo-oesophageal